The Impact of Digitalization on Labor Productivity in the MSME Sector in Makassar City - Andi Idham Danal Ashar; Andi Tenry Sose; Darmawati Manda; Surianti Surianti (Public Resource Innovation Management and Excellence, 2025)
Digitalization has become a major factor in increasing labor efficiency and productivity, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the impact of digitalization on labor productivity in the MSME sector in Makassar City. The research method used is a quantitative approach with data collection through a survey of MSME actors who have adopted digital technology, such as the use of e-commerce, social media, digital financial applications, and business management software. The results of the study show that digitalization has a positive and significant impact on labor productivity, especially in terms of operational efficiency, increasing market access, and financial management. However, challenges such as limited access to technology, lack of digital skills, and implementation costs are still obstacles for some MSMEs. Therefore, support is needed from the government and related parties in the form of training, access to financing, and better technology infrastructure so that digital transformation can be optimized in increasing the competitiveness of MSMEs in Makassar City.